Cytoplasmic Skp2 expression is associated with p-Akt1 and predicts poor prognosis in human breast carcinomas. - Jing Liu (Public Library of Science (PLoS), 2012)
Background S-phase kinase protein 2 (Skp2), an oncogenic protein, is a key regulator in different cellular and molecular processes, through ubiquitin-proteasome degradation pathway. Increased levels of Skp2 are observed in various types of cancer and associated with poor prognosis. However, in human breast carcinomas, the underlying mechanism and prognostic significance of cytoplasmic Skp2 is still undefined. Methods To investigate the role of cytoplasmic Skp2 expression in human breast carcinomas, we immnohistochemically assessed cytoplasmic Skp2, p-Akt1, and p27 expression in 251 patients with invasive ductal carcinomas of the breast. Association of cytoplasmic Skp2 expression with p-Akt1 and p27 was analyzed as well as correspondence with other clinicopathological parameters. Disease-free survival and overall survival were determined based on the Kaplan-Meier method and Cox regression models. Results Cytoplasmic of Skp2 was detected in 165 out of 251 (65.7%) patients. Cytoplasmic Skp2 expression was associated with larger tumor size, more advanced histological grade, and positive HER2 expression. Increased cytoplasmic Skp2 expression correlated with p-Akt1 expression, with 54.2% (51/94) of low p-Akt1-expressing breast carcinomas, but 72.6% (114/157) of high p-Akt1-expressing breast carcinomas exhibiting cytoplasmic Skp2 expression. Elevated cytoplasmic Skp2 expression with low p-Akt1 expression was associated with poor disease-free and overall survival (DFS and OS), and Cox regression models demonstrated that cytoplasmic Skp2 expression was an independent prognostic marker for invasive breast carcinomas. Conclusion Cytoplasmic Skp2 expression is associated with aggressive prognostic factors, such as larger tumor size, and advanced histological grade of the breast cancers. Results demonstrate that combined cytoplasmic Skp2 and p-Akt1 expression may be prognostic for patients with invasive breast carcinomas, and cytoplasmic Skp2 may serve as a potential therapeutic target.